2018
DOI: 10.5851/kosfa.2018.e39
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibiotic Residues and Antibiotic Resistance in Isolates of Chicken Meat in Korea

Abstract: The aim of study was to investigate the correlation between the level of 17 antibiotic residues and 6 antibiotic resistances of Escherichia coli isolates in chicken meats. A total of 58 chicken meats were collected from retail grocery stores in five provinces in Korea. The total detection rate of antibiotic residues was 45% (26 out of 58). Ten out of 17 antibiotics were detected in chicken meats. None of the antibiotics exceeded the maximum residue level (MRLs) in chicken established by the Ministry of Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
1
18
2
Order By: Relevance
“…In addition to its potential to mitigate CH 4 , consumer preference may factor into the acceptance of such a synthetic compound if commercially available. Furthermore, concerns have been raised regarding the potential use of antibiotics because of their residues in final products, which have led to bans in the Republic of Korea since 2011 [ 11 , 12 ]. Therefore, natural plant feed additives that might be environmentally friendly and have a high level of acceptance among consumers are desired to improve livestock productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its potential to mitigate CH 4 , consumer preference may factor into the acceptance of such a synthetic compound if commercially available. Furthermore, concerns have been raised regarding the potential use of antibiotics because of their residues in final products, which have led to bans in the Republic of Korea since 2011 [ 11 , 12 ]. Therefore, natural plant feed additives that might be environmentally friendly and have a high level of acceptance among consumers are desired to improve livestock productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hyo-Ju and Seung-Hak et al used QuEChERS as a pretreatment and then used the LC-MS/MS method to detect 17 antibiotic residues in chicken meat in Korea [34]. Although the sample matrix is complex, the recoveries of 12 antibiotic samples are more than 90%, most of which have relative standard deviations below 15%, and the linear relationship (expressed by the square of the correlation coefficient) is greater than 0.98.…”
Section: Instrument Analysis Methodsmentioning
confidence: 99%
“…Compared with previous studies, the recoveries and relative standard deviations of most antibiotics in chicken meat have satisfactory results in this method. It also has advantages in sensitivity and detection limit (as low as 0.01 g/kg) [34].…”
Section: Instrument Analysis Methodsmentioning
confidence: 99%
“…14 A study conducted among the non-medical students in three universities found that 58.3 % of the 727 students took self-medication in the past six months and metronidazole was the most common drug misused 15 Antibiotic resistance in poultry, animal husbandry and fishing India will be the fourth largest consumer of antibiotics in food animals by 2030. 10 A study conducted in Korea evaluated the presence of antibiotic resistant bacteria in chicken meats which found that 51 E. coli isolates were identified in 51 chicken meats and they were resistant to ampicillin(75%), tetracycline(69%), ciprofloxacin, trimethoprim/ sulfmethaxozole, ceftiofur, amoxicillin/clavulanic acid 16 The trend of using antibiotics as growth promoters in animals started in 1950 s when the drugs procaine penicillin and tetracycline was used in animals like pigs and cows. The use of the antibiotics in fish food contaminates the water ponds leading to transmission of resistance among the exposed organisms.…”
Section: Self-medicationmentioning
confidence: 99%